PEMBUATAN KERUPUK IKAN RED DEVIL (Amphilopus spp.) DI KAMPUNG YOBOI, SENTANI, KABUPATEN JAYAPURA - Gea, Liyatin; Sujarta, Puguh; Mishbach, Imam; Safaati, Sufeni; Tuhumena, Lolita (Pattimura University, 2024)
The red devil fish (Amphilophus spp.) is a carnivorous fish from Nicaragua that is considered a pest due to its predatory nature toward smaller fish. Although it does not have high economic value, this fish reproduces rapidly and threatens the endemic fish population in Lake Sentani, Papua. The endemic fish population has declined due to the increasing population of red devil fish that live in colonies in the littoral zone. Despite its high amino acid content, this fish is less favored due to the abundance of bones. One way to increase its consumption is by processing it into crackers. The method used involves training the community. The goal of this activity is to increase the consumption of red devil fish among the community. The results and achievements of this activity show that the women of Yoboi village successfully utilized the previously underutilized red devil fish by processing it into crackers. This has had a positive impact on maximizing local potential and creating new business opportunities, thereby improving economic welfare. This activity has also enhanced food processing skills within the community.